PENGARUH SUSPENDER TIPE VERTICAL DAN INCLINED TERHADAP KESTABILAN JEMBATAN GANTUNG - Munawir Munawir; Noni Chintya Nasution (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2017)
Suspender of suspension bridge consists of several types including vertical and inclined suspenders, then the formulation of the problem in this study take into account this differences to analyze how the influence of the suspender type on the behavior of the hanging cable which aims to plan the safety structure of the suspension bridge and determine the behavior of the bridge structure related inner and displacement forces. The benefits of this design is to obtain the structure of a suspension bridge that passable for passenger vehicle for both types of suspenders. The modeled bridge structure is 120 m length and 2.5 m width. Design and analysis of a suspension bridge is using SAP2000 version 14 with reference loading refers to SNI 1725-2016. The maximum axial force on the main cable of inclined suspender is larger than the axial force on the vertical suspender, which respectively is 525.83 kN and 872,661 kN, especially on the load combinations which take into account the effect of wind force, axial force of vertical suspender is greater than the inclined suspender which shows that the tension on the vertical cable is larger due to wind load. Based on the displacement of the truss, it was found that the value of each combination of load deflections on the vertical suspenders was much greater than the inclined suspender which is 384 mm in vertical suspenders and 323 mm in suspended suspenders. Pu / ØPn ratio value in the vertical suspender is smaller than the inclined suspender, but the deflection for both types of suspenders has met the permit deflection of L / 200. Based on the calculation, it canbe concluded that suspension bridges with vertical suspenders are safer to the ultimate load, while the inclined load of inclined type is better because of the deflection on the smaller bridge truss.Keywords: Suspension Bridge, Deflection, Capacity Ratio, Inclined Suspender, Vertical Suspender.